Development of Self-Efficacy Learning Management Program in HIV Prevention for At-Risk Youth in the Bangkok Metropolitan Area - Suratavamit, Sorada; Srisiri, Sununta (Journal of Humanities and Social Sciences, Rajapruk University, 2022)
At the present, HIV transmission has still been an important problem in Thailand. HIV prevention needs solutions urgently, especially among At-Risk Youth. This study was to develop for synthesis and evaluate a self-efficacy Learning Management Program in HIV prevention for at-risk youth in the Bangkok Metropolitan Area. Self-efficacy theory by Albert Bandura was applied as a theoretical framework for self-efficacy. This study was divided into three phases: Phase I: developing the program by a systematic review of the literature and using in-depth, semi-structured interviews by Snowball determines with 6 Active sexual youth leadership participants. Phase II: the program’s intervention consisted of 13 active sexual youths with no condom. Phase III: a program evaluation of the effects with 10 participants as phase II. Data were collected by quantitative and qualitative methods. Wilcoxon Signed Rank Test for Matched Paired Deference was used to analyze quantitative data. The results found that: 1. The components of the self-efficacy learning management program in HIV prevention for at-risk youth in the Bangkok metropolitan included 4activities about 1 hour per activity by focusing on mastery experience. Including 1)ransack success/ persuasion/ recall restraint/ spicy phrase or picture activity 2) persuasion pass model/ verify success 3) remind activity and 4) recognization activity/ verify success/ 4 sources of self-efficacy. 2. After joining the program found that the mean pre-test and post-test mean scores were statistically different at the .05 level. The program was developed to be appropriate and enhance self-efficacy in HIV prevention for at-risk youth in Bangkok.